Black water-free sintered activated carbon rod for water purifier and preparation method thereof

CN122916142APending Publication Date: 2026-10-16OLANSI HEALTHCARE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611384398.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0009]针对现有技术的不足,本发明的目的是提供一种净水器用无黑水烧结活性炭棒的制备方法,用于解决现有烧结活性炭棒因表层结构疏松导致炭粉脱落产生黑水、需长时间冲洗方可使用、为提高强度而增加粘结剂用量反而堵塞微孔降低吸附性能、以及长期水压冲击下持续掉粉导致二次污染的技术问题

Benefits of technology

[0030] Another object of the present invention is to provide a black water-free sintered activated carbon rod for water purifiers prepared by the aforementioned preparation method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a kind of sintered activated carbon rod without black water for water purifier and preparation method thereof, belong to water purification equipment consumable technical field.The method includes raw material pretreatment, mixing, hydrophilic modification, gradient sintering, low-temperature compaction setting, surface fine powder treatment, plasma surface treatment and post-processing steps.Two-stage low-temperature plasma surface treatment is used in the application, a dense anti-shedding layer is formed on the surface of the carbon rod, and a gradient dense structure of "inner layer adsorption, surface layer powder locking" is realized.The turbidity is less than 2 NTU when water is first passed through, and it can be used without flushing.Meanwhile, through the synergistic effect of composite adhesive, pore-forming agent and hydrophilic modifier, the iodine adsorption value retention rate is greater than or equal to 95%, and the radial strength is greater than or equal to 95 N / cm, which takes into account high adsorption performance, high mechanical strength and excellent hydrophilicity, and solves the problems of black water, powder loss and flushing water consumption and time consumption of existing sintered activated carbon rod.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of consumables technology for water purification equipment, and more specifically, to a black water-free sintered activated carbon rod for water purifiers and its preparation method. Background Technology

[0002] In household and commercial water purification equipment, activated carbon filter cartridges are widely used to remove residual chlorine, COD, discoloration, odor, and some organic matter from water due to their excellent adsorption performance. Currently, activated carbon rods are mostly produced using sintering or dry extrusion molding, where activated carbon powder is mixed with a polymer binder and then sintered at high temperatures. These carbon rods have advantages such as low cost and large adsorption capacity, and occupy an important position in the water purification field.

[0003] However, traditional sintered activated carbon rods still have the following prominent problems in actual production, logistics and use: (1) Carbon powder shedding leads to "black water" problem and poor user experience: During the preparation, transportation, installation and use of sintered activated carbon rods, fine carbon powder is easily generated between carbon particles due to friction. When water is first turned on, a large amount of carbon powder is washed out with the water flow, resulting in obvious black turbidity in the effluent. Studies have shown that in the existing technology, carbon blocks composed of granular activated carbon (GAC) can cause the initial turbidity to exceed 100 NTU due to carbon powder shedding when water is first turned on. When users see black water flowing out when they first use the product, they often question the purification ability of the water purifier and even refuse to use the product. This "black water" problem has long plagued the industry and seriously affected the user experience and market reputation of the product.

[0004] (2) Conventional processes require prolonged rinsing, which is water-intensive, time-consuming, and poses safety hazards: To solve the aforementioned black water problem, existing products typically require a prolonged water flushing process of 5-10 minutes after leaving the factory or after installation to flush out the free carbon powder inside the carbon rod before normal use. This rinsing process not only wastes a large amount of water resources but also prolongs the user's installation waiting time. More seriously, the prolonged rinsing process poses hygiene and safety hazards—the rinsing water is directly discharged into the sewer or collection container. If the operation is improper or the rinsing is not thorough, the residual carbon powder and potentially carried microorganisms will still affect the quality of the subsequent effluent.

[0005] (3) Excessive use of polymer binders leads to micropore blockage and decreased adsorption performance: To ensure the structural strength and formability of the carbon rod, existing technologies typically require the addition of a high proportion of polymer binders. However, after melting at high temperatures, the binder penetrates into the pores of the activated carbon, blocking a large number of effective adsorption channels. Studies have shown that the binder itself not only lacks any adsorption capacity, but its penetration into the pores of activated carbon also causes a significant decrease in the specific surface area and pore volume of the formed activated carbon. The higher the proportion of binder, the more severe the pore blockage, and the greater the loss of adsorption performance of the carbon rod. How to maximize the preservation of the adsorption performance of activated carbon while ensuring the strength of the carbon rod is a long-standing contradiction faced by the industry.

[0006] (4) Insufficient mechanical strength of carbon particles, resulting in continuous powder shedding under long-term water pressure impact: The mechanical strength of sintered activated carbon rods mainly depends on the "welding" effect of the binder on the carbon particles. However, even with the sintering process, the overall strength of the carbon rods is still limited in the existing technology. Under long-term water pressure impact, the carbon particles gradually break and pulverize due to repeated water flow scouring and friction. When the mechanical strength of granular activated carbon is not high, carbon powder will continuously fall off during water pressure scouring, resulting in a continuous "black water" phenomenon. In addition, the accumulation of detached carbon powder at the outlet may also cause filter element blockage, further shortening the service life of the filter element.

[0007] (5) Existing solutions are merely stopgap measures and do not address the root cause of the problem: Regarding the aforementioned carbon powder shedding issue, existing technologies mainly employ passive interception methods: covering the carbon rod with non-woven fabric or PP cotton, or adding an activated carbon collector at the outlet. While these methods can intercept the shed carbon powder to some extent, they do not fundamentally solve the root cause of carbon powder generation (the inherent defects of the carbon rod itself, such as its loose structure and easy shedding of surface powder). The accumulation of intercepted carbon powder may actually exacerbate filter clogging. Furthermore, some technologies attempt to increase the strength of the carbon rod by increasing the amount of binder, but this inevitably leads to further loss of adsorption performance. The contradiction between strength and adsorption performance, and between surface powder retention and internal flux, has never been effectively balanced.

[0008] In summary, existing sintered activated carbon rod technologies suffer from carbon powder shedding and black water issues during production, logistics, installation, and long-term use. Furthermore, current solutions largely adopt a passive "end-of-pipe interception" approach, failing to achieve fundamental breakthroughs in the material system, structural design, and manufacturing process of the activated carbon rod. Therefore, there is an urgent need to develop a black water-free sintered activated carbon rod that can fundamentally suppress carbon powder shedding, achieve ready-to-use without rinsing, and simultaneously possess high adsorption performance and high mechanical strength. Summary of the Invention

[0009] To address the shortcomings of existing technologies, the purpose of this invention is to provide a method for preparing black water-free sintered activated carbon rods for water purifiers. This method solves the technical problems of existing sintered activated carbon rods, such as black water generation due to carbon powder shedding caused by a loose surface structure, the need for long-term rinsing before use, increased binder dosage to improve strength resulting in blockage of micropores and reduced adsorption performance, and secondary pollution caused by continuous powder shedding under long-term water pressure impact.

[0010] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing black water-free sintered activated carbon rods for water purifiers includes the following steps: (1) Raw material pretreatment: Dry the coconut shell activated carbon until the moisture content is ≤3%; (2) Mixing: By weight, take 100 parts of coconut shell activated carbon dried in step (1), 15-25 parts of composite adhesive, 2-3 parts of pore-forming agent, and 0.3-0.8 parts of lubricant, add them to a high-speed mixer and mix evenly, controlling the mixing temperature to ≤65℃; the composite adhesive is made of ultra-high molecular weight polyethylene and low density polyethylene in a mass ratio of 1:1. (3) Hydrophilic modification: Add 0.2 to 0.5 parts of hydrophilic modifier to the mixture in step (2), stir evenly and then dry; the hydrophilic modifier is a mixed solution of KCl and ZnSO4; (4) Molding and gradient sintering: The mixture from step (3) is loaded into a mold and pressed into shape, and then the mold is sent into a sintering furnace for gradient sintering. (5) Low-temperature compaction and shaping: The green body sintered in step (4) is compacted at 70°C and 15 MPa pressure; (6) Surface micro powder treatment: Take the carbon rod from step (5) out of the mold, place it in a closed environment with a humidity of 75% for 24 h, and then put it in a 90℃ oven for 4 h. (7) Plasma surface treatment: The carbon rod from step (6) is placed in a low-temperature plasma treatment device and subjected to plasma surface treatment in an oxygen-containing atmosphere; (8) Post-processing: Cut the carbon rods from step (7) into the target length, wrap the filter element with non-woven fabric, and seal both ends.

[0011] For the above technical solutions, this invention starts from the idea of ​​"root cause suppression" rather than "end-point interception" and constructs a complete technical path of "formula optimization + bulk phase pore building + surface densification". Specifically: Step (1) removes the adsorbed moisture in the activated carbon by drying to avoid the moisture from vaporizing during high-temperature sintering, which would cause the green body to crack or have an uneven structure; Step (2) uses a two-component compound design of the composite adhesive, which uses ultra-high molecular weight polyethylene to provide excellent bonding strength and wear resistance, while using low-density polyethylene to adjust the melt flowability, so that the adhesive can uniformly coat the carbon particles without excessively blocking the pores during sintering, thus taking into account both mechanical strength and adsorption performance; Step (3) pre-modifies the surface of the carbon particles by using a hydrophilic modifier. Polar sites are introduced into the internal channels of the carbon rod to lay the foundation for low-resistance filtration during subsequent water flow. Steps (4) to (6) involve gradient sintering, low-temperature compaction, and humidification-drying treatment to gradually shape the carbon rod blank and form a preliminary bulk pore structure. Step (7) is the core improvement of this invention. Plasma treatment is introduced into the surface of the formed carbon rod, and the high-energy particle bombardment effect of plasma is used to achieve surface polymer cross-linking and pore shrinkage, forming a dense anti-detachment layer on the surface without changing the high porosity adsorption structure of the inner layer. This "loose inside and tight outside" gradient structure allows the surface layer of the carbon rod to effectively lock the internal carbon powder during the first water flow, achieving ready-to-use without rinsing, while the inner layer maintains sufficient adsorption capacity, solving the contradiction of "incompatibility between strength and adsorption performance" in the prior art.

[0012] Preferably, the coconut shell activated carbon in step (1) has an iodine value ≥1050 mg / g and is composed of 80-200 mesh carbon powder and 200-250 mesh carbon powder, wherein the mass percentage of 80-200 mesh carbon powder is 65%-85% and the mass percentage of 200-250 mesh carbon powder is 15%-35%.

[0013] For the above technical solutions, the adsorption performance of activated carbon is directly related to its iodine value. An iodine value ≥1050 mg / g ensures that the raw material possesses excellent intrinsic adsorption performance. Regarding particle size distribution, existing technologies typically employ a single particle size or a narrow particle size distribution, resulting in numerous voids when carbon particles are packed together. This not only reduces the density and strength of the green body but also increases the filling requirement of the binder. This invention employs a bimodal gradation of 80–200 mesh (65%–85%) and 200–250 mesh (15%–35%). Coarse particles form the main framework of the green body, while fine particles fill the voids between the coarse particles, maximizing the packing density. The advantages of this gradation design are: higher green body strength and lower porosity fluctuations can be obtained with the same amount of binder, providing a structurally uniform green body foundation for subsequent sintering and plasma densification. It also reduces the amount of binder required to fill the pores, which is beneficial for maintaining the adsorption performance of activated carbon.

[0014] Preferably, the intrinsic viscosity of the ultra-high molecular weight polyethylene in step (2) is 1500-3500 ml / g, and the melt index of the low density polyethylene is 0.1-5 g / 10min; the pore-forming agent is composed of sodium bicarbonate and starch, wherein the mass percentage of sodium bicarbonate is 97% and the mass percentage of starch is 3%; the lubricant is polyethylene wax or food-grade stearic acid.

[0015] For the above technical solution, the intrinsic viscosity of ultra-high molecular weight polyethylene (UHMWPE) reflects its molecular weight. An intrinsic viscosity of 1500–3500 ml / g corresponds to a molecular weight sufficient to form a high-strength three-dimensional network structure after sintering, providing the carbon rod with the required resistance to water pressure impact. Low-density polyethylene (LDPE) has a melt index of 0.1–5 g / 10min, exhibiting moderate fluidity at the sintering temperature. This allows for sufficient wetting of the carbon particle surface to enhance interfacial bonding without excessive flow that could clog micropores. The 1:1 ratio of these two components achieves a synergistic effect of "high-strength skeleton + moderate flow filling." Regarding the pore-forming agent, the combination of 97% sodium bicarbonate and 3% starch utilizes the difference in their decomposition temperatures to achieve a stepped pore-forming effect (sodium bicarbonate begins to decompose at 100–150℃ to produce CO2 gas for pore formation, while starch carbonizes at higher temperatures to form interconnected channels), resulting in a more uniform pore distribution and avoiding the problem of pore size concentration caused by a single pore-forming agent. The addition of lubricant aims to reduce the frictional resistance between the material and the mold wall, ensuring that the mixture can uniformly fill the mold during molding, reducing the risk of delamination and uneven density.

[0016] Preferably, the mass concentration of the KCl and ZnSO4 mixed solution in step (3) is 10% to 30%, the mass ratio of KCl to ZnSO4 is 1:2, and the stirring time is 10 to 16 h.

[0017] For the above technical solution, both KCl and ZnSO4 are food-grade inorganic salts, safe and non-toxic, meeting the hygiene requirements for water-related products. K⁺ and Zn²⁺ ions in aqueous solution can gently etch and activate the activated carbon surface, introducing oxygen-containing polar groups and improving the hydrophilicity of the carbon surface. Simultaneously, ZnSO4 can be partially converted into ZnO nanocrystals during subsequent sintering, anchoring them to the inner walls of the carbon pores, further enhancing hydrophilicity and antibacterial properties. A mass concentration of 10%–30% and a mass ratio of 1:2 are optimized mixing ranges; too low a concentration will not have a significant modification effect, while too high a concentration may clog micropores. The higher proportion of ZnSO4 than KCl is to utilize the stronger polarization ability of Zn²⁺ to more effectively change the charge distribution on the carbon surface. Stirring and mixing for 10–16 hours ensures that the modifier fully penetrates into the micropores of the carbon particles, achieving uniform modification, rather than only acting on the outer surface of the particles.

[0018] Preferably, the pressing pressure in step (4) is 10–30 MPa; the gradient sintering includes the following stages: Stage 1: Heat to 100-150℃ at a heating rate of 30-50℃ / h, and hold for sintering for 30 min; Stage 2: Increase the temperature to 180-220℃ at a heating rate of 50-80℃ / h, and hold for sintering for 75 minutes; Stage 3: Cool down to 65-80℃ at a rate of 30-60℃ / h, and hold for sintering for 30 minutes.

[0019] Preferably, the pressing pressure in step (4) is 20 MPa, and the sintering temperature in stage two is 220°C.

[0020] For the above technical solution, the selection of the pressing pressure of 10–30 MPa is based on the balance between the green body density and porosity: if the pressure is too low (<10 MPa), the green body density is insufficient, the contact between particles is inadequate, and the strength after sintering is poor; if the pressure is too high (>30 MPa), the particles are excessively crushed, the packing is too dense, the porosity decreases significantly, and the adsorption flux is affected. This invention preferably uses this pressure range to control the green body density at 0.9–1.1 g / cm³, leaving sufficient space for porosity adjustment during subsequent sintering.

[0021] The gradient sintering process demonstrates the precise control of the temperature curve in this invention: Stage 1 involves a slow heating rate to 100–150°C to ensure uniform heating of the green body, allowing sodium bicarbonate in the pore-forming agent to decompose and release gas under controlled conditions, while slowly removing residual moisture and volatile components to prevent rapid gas generation that could cause cracking of the green body; Stage 2 involves a slightly faster heating rate to 180–220°C and holding at this temperature for 75 minutes. This temperature range is the optimal melting range for the composite adhesive, allowing ultra-high molecular weight polyethylene to fully melt and crosslink at this temperature, forming a robust three-dimensional network structure. Simultaneously, the starch is completely carbonized to form secondary pores. The coordinated control of temperature and time in this stage is crucial in determining the final strength and porosity of the carbon rod; Stage 3 involves a slow cooling rate of 30–60°C / h to 65–80°C to eliminate internal stress generated during high-temperature sintering, prevent microcracks caused by rapid cooling, and allow the adhesive to gradually solidify and set during the cooling process. Compared to existing isothermal sintering or simple two-stage sintering technologies, the three-stage gradient design can more precisely control the physicochemical processes at each stage, achieving synergistic optimization of "pore formation-sintering and solidification-stress relief".

[0022] Preferably, the plasma surface treatment in step (7) uses a low-temperature plasma jet treatment device, the treatment atmosphere is air or oxygen, the gas flow rate is 50-100 cc / min, and the treatment time is 2-10 min.

[0023] For the above technical solution, the low-temperature plasma jet treatment device can operate under atmospheric pressure without a vacuum system, making it suitable for continuous industrial production. The jet pattern facilitates scanning and uniform treatment of the cylindrical carbon rod surface. The treatment atmosphere is either air or oxygen, aiming to utilize the active oxygen species (O atoms, O⁺, O₃, etc.) in the oxygen-containing plasma to achieve a dual function: firstly, removing loose carbon powder and low-molecular-weight organic matter from the surface through oxidation etching; secondly, introducing oxygen-containing polar groups (such as C=O, -COOH, -OH) into the carbon rod surface to improve surface hydrophilicity, allowing water to quickly wet the surface and pass through smoothly during the initial water flow, reducing water flow resistance. A gas flow rate of 50–100 cc / min ensures stable plasma jet and sufficient concentration of active species. Too low a flow rate results in insufficient plasma density and insignificant treatment effect; too high a flow rate leads to jet turbulence and decreased treatment uniformity. The processing time of 2–10 min is set based on a balance between densification effect and processing efficiency. If the time is too short, the surface cross-linking reaction will be incomplete, and the thickness of the dense layer will be insufficient; if the time is too long, excessive etching may damage the surface structure or even cause quality loss. The core value of this step is that the plasma treatment only acts on the surface depth of the carbon rod, without changing the high porosity adsorption structure already formed inside the carbon rod, thus achieving the functional differentiation of "dense surface for powder locking and high porosity adsorption inside".

[0024] Preferably, the plasma surface treatment in step (7) is a two-stage process: First stage: The distance from the plasma jet outlet to the carbon rod surface is 10-20 mm, and the carbon rod surface is uniformly treated at a scanning speed of 10-20 mm / s for 2-5 min. Second stage: Adjust the distance from the plasma jet outlet to the carbon rod surface to 150-200 mm and continue processing for 2-4 minutes.

[0025] The two-stage processing design of the above technical solution reflects the invention's deep understanding of the relationship between plasma interaction distance and effect. In the first stage (close-range processing), the distance from the jet outlet to the carbon rod surface is only 10-20 mm. At this time, the plasma jet has high energy density and a large flux of high-energy particles, mainly resulting in physical bombardment and cross-linking reactions. High-energy ions and VUV photons directly act on the surface polyethylene molecular chains, breaking CC / CH bonds and generating a large number of free radicals. These free radicals rapidly cross-link to form a three-dimensional network structure. The core objective of close-range processing is to achieve surface densification (pore shrinkage and enhanced cross-linking). At the same time, high-energy bombardment can also inject some carbon species into the inner walls of the surface pores, further filling the pores. The processing time of 2-5 minutes, combined with a scanning speed of 10-20 mm / s, ensures that the entire outer surface of the carbon rod is uniformly covered, avoiding local over-processing or unprocessed areas.

[0026] In the second stage (long-distance processing), the distance is increased to 150–200 mm. At this stage, the jet energy is significantly reduced, the physical bombardment effect of high-energy particles weakens, and spark discharge disappears. However, long-lived active species in the plasma can still reach the carbon rod surface, mainly undergoing chemical modification by grafting oxygen-containing polar groups onto the surface polymer chains, thus improving hydrophilicity and wettability. The core objective of long-distance processing is to improve the surface chemical properties rather than alter the physical structure. This two-stage processing achieves a synergistic effect of "physical densification + chemical hydrophilization," which is difficult to achieve simultaneously with single-stage processing.

[0027] Furthermore, the sequence of performing close-range densification in the first stage and then long-range hydrophilic modification in the second stage is intentionally designed: if long-range hydrophilic modification is performed first, the polar groups introduced on the surface may be destroyed or removed in subsequent high-energy bombardment, resulting in a loss of hydrophilic effect; while completing cross-linking densification on the unmodified surface first, and then performing mild chemical grafting on the densified surface, both effects can be preserved to the greatest extent.

[0028] Preferably, the carbon rod after plasma surface treatment in step (7) has a gradient dense structure, with the inner layer being a porous adsorption layer with a porosity of 45% to 55%; and the outer layer being a dense anti-detachment layer formed by plasma treatment with a thickness of 0.3 to 0.8 mm and a porosity of 25% to 35%.

[0029] For the above technical solution, after two-stage plasma treatment, the carbon rod forms a gradient structure in the thickness direction: the inner layer maintains a high porosity of 45% to 55% to ensure the adsorption capacity and water flux of the activated carbon; the porosity of the surface layer within the thickness range of 0.3 to 0.8 mm is reduced to 25% to 35%, forming a physically dense layer. The core advantages of this gradient structure are: (1) The pore size of the dense surface layer is reduced, which physically blocks the path of internal carbon particles to migrate outward, thus realizing the "powder locking" function. Even if a small amount of carbon powder is generated in the inner layer due to water flow, it cannot escape through the dense surface pores. The turbidity of the first water flow can be reduced to <2NTU, and it can be used without rinsing; (2) The dense layer accounts for only a very small part of the total wall thickness of the carbon rod, and the vast majority of the inner layer still maintains high porosity. Therefore, the adsorption capacity and flux loss are minimal, overcoming the defect of the existing technology that increases the amount of binder to improve strength and causes complete pore blockage; (3) After the surface layer is modified by plasma hydrophilicity, water flow can easily flow from the inside of the carbon rod to the outside, avoiding the problem of "surface skin" and sudden drop in flux caused by the dense layer being too dense, thus unifying the seemingly contradictory functions of "powder locking" and "water flow".

[0030] Another object of the present invention is to provide a black water-free sintered activated carbon rod for water purifiers prepared by the aforementioned preparation method.

[0031] Compared with the prior art, this application has the following beneficial effects: (1) Through low-temperature plasma two-stage surface treatment, a dense anti-detachment layer of 0.3 to 0.8 mm is formed on the surface of the carbon rod, reducing the surface porosity from 45% to 55% to 25% to 35%, and the turbidity of the first water flow is <2 NTU, so it can be used without rinsing, thus solving the black water problem from the root; (2) The compound design of the composite adhesive (UHMWPE and LDPE in a 1:1 ratio) and the step-type pore-forming effect of the pore-forming agent make the iodine adsorption value retention rate ≥95%, and the inner layer porosity maintained at 45% to 55%, taking into account both high adsorption capacity and high flux; (3) The gradient dense structure makes the radial strength ≥95 N / cm and the bursting pressure ≥1.9 MPa, does not deform or shed powder under long-term water pressure impact; (4) The plasma oxygen atmosphere treatment introduces polar groups simultaneously, with a contact angle ≤38°, improving hydrophilicity, stable flux and small flow rate attenuation; (5) All raw materials are food grade, meeting the hygiene and safety requirements of water-related products, and each process is compatible with existing industrial mass production equipment, with good industrialization prospects. Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the following detailed and specific implementation description is provided in conjunction with actual industrial application scenarios. The parameters, equipment selection, and testing standards set in this embodiment are all formulated with reference to the mature configurations of existing industrial mass production lines and can be directly adapted to the needs of mass production lines.

[0033] The specifications of the raw materials used in the various embodiments and comparative examples of this invention are as follows: Table 1 Raw Material Specifications Example 1

[0034] A method for preparing black water-free sintered activated carbon rods for water purifiers includes the following steps: (1) Raw material pretreatment: Dry coconut shell activated carbon at 120℃ until the moisture content is ≤3%.

[0035] (2) Mixing: By weight, take 100 parts of dried coconut shell activated carbon, 20 parts of composite adhesive, 2.5 parts of pore-forming agent, and 0.5 parts of lubricant, and add them to a high-speed mixer. First, stir and mix at 150 r / min for 8 min, then stir and mix at 500 r / min for 4 min, controlling the mixing temperature to ≤65℃. The composite adhesive is composed of ultra-high molecular weight polyethylene and low-density polyethylene in a mass ratio of 1:1; the pore-forming agent is composed of 97% sodium bicarbonate and 3% starch; and the lubricant is polyethylene wax.

[0036] (3) Hydrophilic modification: Add 0.3 parts of hydrophilic modifier to the mixture in step (2), stir and soak for 12 h, filter and dry. The hydrophilic modifier is a mixed solution of KCl and ZnSO4 with a mass concentration of 20% and a mass ratio of KCl to ZnSO4 of 1:2.

[0037] (4) Molding and gradient sintering: The mixture from step (3) is loaded into a mold and pressed into shape under a pressure of 20 MPa; then the mold is sent into a precision temperature-controlled sintering furnace for gradient sintering according to the temperature control method in Table 2: Table 2 Sintering Temperature Control Program

[0038] (5) Low-temperature compaction and shaping: The green body after sintering in step (4) is compacted at 70℃ and 20 MPa pressure.

[0039] (6) Surface micro powder treatment: Take the carbon rod from step (5) out of the mold, place it in a closed environment with a humidity of 75% for 24 h, and then put it in a 90℃ oven for 4 h.

[0040] (7) Plasma surface treatment: The carbon rod from step (6) is placed in a low-temperature plasma jet treatment device and subjected to two-stage treatment in an oxygen atmosphere according to the plasma method in Table 3, with a gas flow rate of 80 cc / min. Table 3 Plasma Processing Procedure

[0041] (8) Post-processing: Cut the carbon rods from step (7) into carbon cores with a target length of 175 mm, an outer diameter of 30 mm, and an inner diameter of 12 mm. Wrap the filter cores with food-grade 100 g / m² PP meltblown nonwoven fabric and seal both ends.

[0042] Example 2 The only difference from Example 1 is that the amount of composite adhesive used in step (2) is 25 parts, and the other process parameters are exactly the same as those in Example 1.

[0043] Example 3 The only difference from Example 1 is that the amount of composite adhesive used in step (2) is 15 parts, and the other process parameters are exactly the same as those in Example 1.

[0044] Example 4 The only difference from Example 1 is that the sintering temperature in stage two of step (4) is 210°C, and the other process parameters are exactly the same as those in Example 1.

[0045] Example 5 The only difference from Example 1 is that the sintering temperature in stage two of step (4) is 180°C, and the other process parameters are exactly the same as those in Example 1.

[0046] Example 6 The only difference from Example 1 is that the total time for plasma surface treatment in step (7) is 6 min (4 min in the first stage and 2 min in the second stage), and the other process parameters are exactly the same as in Example 1.

[0047] Comparative Example 1 The only difference from Example 1 is that step (7) plasma surface treatment is omitted, while the other process parameters are exactly the same as in Example 1.

[0048] Comparative Example 2 The only difference from Example 1 is that the plasma treatment only performs the first stage (15 mm from the jet outlet to the carbon rod surface, treatment for 3 min), without performing the second stage of long-distance treatment. All other process parameters are exactly the same as in Example 1.

[0049] Comparative Example 3 The only difference from Example 1 is that the plasma treatment is only performed in the second stage (180 mm from the jet outlet to the carbon rod surface, 3 min), without the first stage of close-range treatment. All other process parameters are exactly the same as in Example 1.

[0050] Comparative Example 4 The only difference from Example 1 is that the order of the two-stage processing is reversed, that is, the long-distance processing is performed first, and then the short-distance processing is performed. All other process parameters are exactly the same as in Example 1.

[0051] Comparative Example 5 The only difference from Example 1 is that the plasma treatment atmosphere is changed from oxygen to nitrogen, while the other process parameters are exactly the same as in Example 1.

[0052] Comparative Example 6 The only difference from Example 1 is that the surface micro powder treatment in step (6) is completely omitted. After low-temperature compaction and shaping, the carbon rod does not undergo 75% humidity standing for 24 hours and 90℃ oven drying for 4 hours, but directly enters plasma treatment. Other process parameters are exactly the same as in Example 1.

[0053] Comparative Example 7 The only difference from Example 1 is that no pore-forming agent is added in step (2), while the other process parameters are exactly the same as in Example 1.

[0054] Comparative Example 8 The only difference from Example 1 is that the amount of pore-forming agent in step (2) is increased to 6 parts, while the other process parameters are exactly the same as in Example 1.

[0055] Comparative Example 9 The only difference from Example 1 is that the pore-forming agent in step (2) is only sodium bicarbonate and does not contain starch. Other process parameters are exactly the same as in Example 1.

[0056] Comparative Example 10 The only difference from Example 1 is that the pore-forming agent in step (2) is only starch and does not contain sodium bicarbonate. Other process parameters are exactly the same as in Example 1.

[0057] Comparative Example 11 The only difference from Example 1 is that in step (1), the mass percentage of coarse powder of 80-200 mesh is 95%, and the mass percentage of fine powder of 200-250 mesh is 5%. Other process parameters are exactly the same as in Example 1.

[0058] Comparative Example 12 The only difference from Example 1 is that in step (1), the mass percentage of coarse powder of 80-200 mesh is 40%, and the mass percentage of fine powder of 200-250 mesh is 60%. Other process parameters are exactly the same as in Example 1.

[0059] Comparative Example 13 The only difference from Example 1 is that in step (1), all activated carbon powder with a single particle size of 80-200 mesh is used, and no fine powder of 200-250 mesh is used. Other process parameters are exactly the same as in Example 1.

[0060] Comparative Example 14 The only difference from Example 1 is that no lubricant is added in step (2), while the other process parameters are exactly the same as in Example 1.

[0061] Comparative Example 15 The only difference from Example 1 is that the amount of lubricant used in step (2) is increased to 2 parts, while the other process parameters are exactly the same as in Example 1.

[0062] Comparative Example 16 The only difference from Example 1 is that no hydrophilic modifier is added in step (3), and the other process parameters are exactly the same as in Example 1.

[0063] Comparative Example 17 The only difference from Example 1 is that the mass concentration of the KCl and ZnSO4 mixed solution in step (3) is 50%, and the other process parameters are exactly the same as those in Example 1.

[0064] Comparative Example 18 The only difference from Example 1 is that the mass concentration of the KCl and ZnSO4 mixed solution in step (3) is 5%, while the other process parameters are exactly the same as in Example 1.

[0065] Comparative Example 19 The only difference from Example 1 is that the hydrophilic modifier in step (3) is only KCl solution (20% mass concentration), and the other process parameters are exactly the same as in Example 1.

[0066] Comparative Example 20 The only difference from Example 1 is that the hydrophilic modifier in step (3) is only ZnSO4 solution (20% mass concentration), and the other process parameters are exactly the same as in Example 1.

[0067] Comparative Example 21 The only difference from Example 1 is that the stirring and impregnation time in step (3) is shortened to 1 h, while the other process parameters are exactly the same as in Example 1.

[0068] Comparative Example 22 The only difference from Example 1 is that the stirring and impregnation time in step (3) is extended to 24 h, while the other process parameters are exactly the same as in Example 1.

[0069] Comparative Example 23 The only difference from Example 1 is that the composite adhesive in step (2) is replaced with a single ultra-high molecular weight polyethylene (UHMWPE), while the other process parameters are exactly the same as in Example 1.

[0070] Comparative Example 24 The only difference from Example 1 is that the composite adhesive in step (2) is replaced with a single low-density polyethylene (LDPE), while the other process parameters are exactly the same as in Example 1.

[0071] The only difference between Comparative Example 25 and Example 1 is that the mass ratio of UHMWPE to LDPE in step (2) is changed from 1:1 to 3:1 (i.e., 15 parts of HMWPE and 5 parts of LDPE). Other process parameters are exactly the same as in Example 1.

[0072] Comparative Example 26 The only difference from Example 1 is that the mass ratio of UHMWPE to LDPE in step (2) is changed from 1:1 to 1:3 (i.e., 5 parts of UHMWPE and 15 parts of LDPE). The other process parameters are exactly the same as in Example 1.

[0073] The only difference between Comparative Example 27 and Example 1 is that the sintering temperature in stage two of step (4) is increased to 260°C, while the other process parameters are exactly the same as those in Example 1.

[0074] Comparative Example 28 The only difference from Example 1 is that the sintering temperature in step (4) of stage two is reduced to 160°C, while the other process parameters are exactly the same as those in Example 1.

[0075] Comparative Example 29 The only difference from Example 1 is that the total plasma surface treatment time in step (7) is extended to 20 min (10 min in the first stage + 10 min in the second stage), while the other process parameters are exactly the same as in Example 1.

[0076] Comparative Example 30 The only difference from Example 1 is that after the second stage sintering in step (4), the third stage slow cooling is not carried out, but instead the cold air is used to quickly cool to room temperature. Other process parameters are exactly the same as in Example 1.

[0077] The samples prepared by the above method were subjected to performance tests. Six groups of test samples (Examples 1-6) and 30 groups of comparative samples (Examples 1-30) were set up, with five parallel carbon rod filter elements in each group. The test results were taken as the arithmetic mean of the test data of the five samples, and outliers were removed. All samples were treated by removing the outer packaging non-woven fabric and sealing both ends to obtain the carbon rod cores for material performance testing. Completely assembled filter elements (with the non-woven fabric and end caps retained) were used for water flow performance and leaching safety performance testing. Through multi-dimensional performance testing, the synergistic effect of the formulation, preparation process, and gradient dense structure of this invention on the carbon rod's powder-locking and black water prevention, mechanical strength, adsorption performance, and hydrophilicity was verified.

[0078] Test 1: Carbon powder shedding and black water suppression performance (1) Turbidity of 2L of water during initial water flow: Refer to T / DZJN 20-2020 "Carbon rods and carbon rod filter cartridges for household and similar drinking water treatment devices", with an inlet water pressure of 0.24 MPa and no pre-rinsing of the sample; collect water samples when water flow reaches 2L and measure the turbidity of the water samples using a turbidity meter; Objective of this invention: Turbidity of 2L of water during initial water flow < 2 NTU.

[0079] (2) Dry weight of carbon powder detached during the first water flow: All the water from the first water flow is vacuum filtered through a 0.45μm aqueous filter membrane. The filter membrane is dried in an oven at 105℃ until constant weight. The difference in mass before and after filtration is the dry weight of the detached carbon powder, in mg.

[0080] (3) Turbidity of effluent after pressure cycling aging: Refer to the pressure cycling test method of GB / T 30306-2024 "Drinking water treatment core for household and similar purposes", complete 1000 pressure alternating cycles between 0 and 0.3 MPa; after the cycle, without pre-rinsing, water is passed through at a pressure of 0.24 MPa, 2L of effluent is collected, and the turbidity of the effluent is measured to evaluate the ability to resist powder shedding and secondary black water under long-term water pressure impact.

[0081] (4) Dense layer thickness test: Cut the carbon rod radially and measure the thickness of the surface dense anti-detachment layer using an optical microscope; the target dense layer thickness of the present invention is 0.3 to 0.8 mm.

[0082] Test 2: Performance of Gradient Pore Structure (1) Inner layer porosity and surface porosity: According to GB / T 24203-2009 "Determination of True Density and True Porosity of Carbon Materials" boiling method; take surface layer slices and inner core samples of carbon rods respectively, and test the surface porosity and inner layer porosity respectively, in %. Objective of this invention: inner layer porosity 45-55%, surface porosity 25-35%.

[0083] Test 3: Mechanical Properties (1) Radial compressive breaking strength: Remove the outer non-woven fabric from the intact carbon rod core, place it on a universal testing machine and apply radial lateral pressure, record the maximum load when the carbon rod breaks, and calculate the radial compressive strength, unit N / cm.

[0084] (2) Bursting pressure: Refer to T / DZJN 20-2020, seal one end of the carbon rod core, slowly increase the inlet water pressure, and record the water pressure when the carbon rod cracks and leaks. This is the bursting pressure, in MPa.

[0085] Test 4: Adsorption and water flow performance (1) Iodine adsorption value of shaped carbon rods: According to GB / T 12496.8-2015 "Test Methods for Iodine Adsorption Value of Wood Activated Carbon", the carbon rod core was crushed and ground to obtain the sample for testing, and the unit was mg / g; to characterize the microporous adsorption and retention level.

[0086] (2) Initial water flux: With a fixed inlet pressure of 0.24 MPa, the volumetric flow rate of pure water through the carbon rod filter element was measured, and the water flux was converted to L / (h・bar) to evaluate whether the dense surface layer caused an excessive increase in water flow resistance.

[0087] Test 5: Surface hydrophilicity (1) Static water contact angle: Refer to the test method of solid sample in GB / T 36086-2018 "Test method for contact angle of nanotechnology powder", use a contact angle measuring instrument to drop pure water on a flat position on the outer surface of the carbon rod and measure the static water contact angle, in °; the smaller the contact angle, the better the hydrophilicity.

[0088] The test data for each embodiment and each comparative example are shown in Tables 4 and 5.

[0089] Table 4 Test data for each embodiment and each comparative example I

[0090] Table 5 Test data for each embodiment and comparative example II

[0091] As shown in Tables 4 and 5, the initial turbidity of the water in Examples 1 to 6 is far below the industry standard of 2 NTU, the surface porosity is lower than the corresponding inner porosity, and the thickness of the dense layer is all within the range of 0.3 to 0.8 mm, forming a clear gradient dense structure. The radial strength and burst pressure are both higher than the normal operating pressure of the water purifier, the iodine adsorption value (985 to 1100 mg / g) retention rate is ≥95%, and the contact angle (31° to 38°) is far lower than that of the hydrophobic surface without hydrophilic modification. This proves that all examples have achieved a combination of no black water, no rinsing, high adsorption, high strength and good hydrophilicity. From the perspective of variable gradient, Example 1→2 (increased binder) showed an increase in strength and a decrease in adsorption and flux; Example 1→3 (decreased binder) showed a decrease in strength and an increase in adsorption and flux; Example 1→4→5 (decreased sintering temperature) showed a decrease in strength and an increase in flux; Example 1→6 (extended near-field plasma treatment time) showed an increase in the thickness of the dense layer, a decrease in flux, and an increase in the contact angle.

[0092] Comparative Example 1, which completely omitted plasma treatment, had almost equal porosity between the surface and inner layers, lacking a gradient structure. Its turbidity was tens of NTU higher than in Example 1, and the contact angle exhibited a clear hydrophobic characteristic, demonstrating that the untreated carbon rod had a loose surface and lacked the ability to retain carbon dust. Comparative Example 2, which only underwent short-range treatment while omitting long-range hydrophilic modification, formed a dense layer and significantly improved turbidity, but the contact angle remained high and the water flux was significantly low. This indicates that physical densification without chemical hydrophilic modification resulted in high flow resistance and insufficient flux. Comparative Example 3, which only underwent long-range treatment while omitting short-range densification, exhibited good hydrophilicity but lacked a dense layer. Its turbidity was on the same order of magnitude as Comparative Example 1, demonstrating that hydrophilic modification without a physical dust-retaining layer cannot effectively suppress carbon dust shedding. Comparative Example 4 reversed the two-stage order, resulting in a significantly thinner dense layer and insufficient surface densification. Turbidity and contact angle were both inferior to Example 1, demonstrating that the "near-to-far" order cannot be reversed. The hydrophilic groups introduced first will be destroyed and hinder cross-linking during subsequent high-energy bombardment. Comparative Example 5 used nitrogen instead of an oxygen-containing atmosphere. Although a dense layer was formed and turbidity was acceptable, the contact angle remained high and the water flux was severely low. This indicates that while nitrogen can achieve physical cross-linking, it cannot effectively introduce oxygen-containing polar groups, and the hydrophilic modification effect is far inferior to that of an oxygen-containing atmosphere.

[0093] Comparative Example 6, which omitted surface micronization treatment, showed higher turbidity and carbon powder shedding than Example 1. The dense layer was thinner, the surface densification was insufficient, and the contact angle was also higher than in Example 1. This indicates that the untreated carbon rod surface contained loose carbon powder and burrs, which were themselves sources of shedding and interfered with the uniformity of the plasma. The synergistic relationship of "first eliminating hidden dangers, then building density" is indispensable.

[0094] Comparative Example 7, without any pore-forming agent, showed a significant decrease in both inner porosity and iodine adsorption value, resulting in severely insufficient water flux. This indicates that without a pore-forming agent, sufficient adsorption channels cannot be formed inside the carbon rod. Comparative Example 8, with excessive pore-forming agent, led to overdevelopment of pores, resulting in a significant decrease in strength and an increase in turbidity, verifying the necessity of an upper limit on the dosage. Comparative Example 9, using only NaHCO3, and Comparative Example 10, using only starch, were inferior to Example 1 in terms of strength, porosity, and iodine adsorption, respectively, demonstrating the irreplaceable nature of the NaHCO3 / starch composite system in terms of stepped pore formation and pore connectivity.

[0095] Comparative Example 11, with its excessively high proportion of coarse powder, and Comparative Example 13, which used a single particle size, both showed significantly insufficient strength and a marked increase in turbidity. This indicates that the absence of fine powder prevents the filling of voids between coarse particles, resulting in low bulk density and decreased strength. Comparative Example 12, with its excessively high proportion of fine powder, showed a decrease in inner layer porosity and iodine adsorption, as well as a reduction in water flux. This suggests that excessive fine powder leads to over-density packing and overfilling of some micropores. These three sets of data collectively validate the necessity of a 65%–85% coarse powder and 15%–35% fine powder composition in a bimodal gradation.

[0096] Comparative Example 14, without added lubricant, showed decreased strength and increased turbidity; Comparative Example 15, with excessive lubricant, showed further performance degradation. This indicates that insufficient lubricant leads to defects in the green body, while excessive lubricant results in decomposition residues forming a weak bonding layer at the particle interface, both of which reduce strength and powder retention capacity.

[0097] Comparative Example 16, without the addition of a hydrophilic modifier, showed significant deterioration in both water flux and contact angle, but turbidity and strength remained essentially unchanged. This indicates that the function of the hydrophilic modifier is independent of physical powder retention and mechanical strength, specifically acting on water flow performance. In Comparative Example 17, an excessively high concentration led to a severe decrease in iodine adsorption and flux. In Comparative Example 18, an excessively low concentration resulted in a still high contact angle and insufficient modification effect. Comparative Examples 19 (KCl only) and 20 (ZnSO4 only) showed lower contact angles and fluxes than Example 1, demonstrating that the composite system is superior to the single-component system. In Comparative Example 21, an excessively short impregnation and mixing time resulted in a high contact angle. In Comparative Example 22, an excessively long impregnation time improved hydrophilicity but slightly decreased iodine adsorption.

[0098] For Comparative Examples 23–26, these four sets of comparative examples formed a relatively complete UHMWPE content gradient. Single UHMWPE exhibited the highest strength but increased turbidity (poor flowability leading to uneven coating), while single LDPE showed severely insufficient strength and high turbidity (excessive flowability leading to excessive pore blockage). Neither of the two ratios deviating from 1:1 achieved the balance between strength and turbidity seen in Example 1. This confirms that 1:1 is the balance point of "high strength + high adsorption + low turbidity".

[0099] In Comparative Example 27, excessively high temperature led to over-melting of the adhesive and severe pore blockage, resulting in decreased iodine adsorption and water flux. Although the turbidity was low, this was at the expense of adsorption and flux. In Comparative Example 28, excessively low temperature resulted in insufficient adhesive melting, severely insufficient strength, and increased turbidity. Combining Examples 1, 4, and 5, the complete temperature gradient demonstrates that 180–220°C is the optimal window for balancing strength, adsorption, and powder retention.

[0100] Comparative Example 29: The plasma treatment time was too long, resulting in an abnormally thickened dense layer and an excessively dense surface layer, leading to a severe decrease in water flux. This indicates that although overtreatment can further reduce turbidity, the flux loss is unacceptable. Comparative Example 30: The rapid cooling method resulted in microcracks that caused a decrease in strength and an increase in turbidity, verifying the necessity of the three-stage slow cooling to eliminate internal stress and prevent microcracks.

[0101] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing black water-free sintered activated carbon rods for water purifiers, characterized in that, Includes the following steps: (1) Raw material pretreatment: Dry the coconut shell activated carbon until the moisture content is ≤3%; (2) Mixing: By weight, take 100 parts of coconut shell activated carbon dried in step (1), 15-25 parts of composite adhesive, 2-3 parts of pore-forming agent, and 0.3-0.8 parts of lubricant, add them to a high-speed mixer and mix evenly, controlling the mixing temperature to ≤65℃; the composite adhesive is made of ultra-high molecular weight polyethylene and low density polyethylene in a mass ratio of 1:

1. (3) Hydrophilic modification: Add 0.2 to 0.5 parts of hydrophilic modifier to the mixture in step (2), stir evenly and then dry; the hydrophilic modifier is a mixed solution of KCl and ZnSO4; (4) Molding and gradient sintering: The mixture from step (3) is loaded into a mold and pressed into shape, and then the mold is sent into a sintering furnace for gradient sintering. (5) Low-temperature compaction and shaping: The green body sintered in step (4) is compacted at 70°C and 15 MPa pressure; (6) Surface micro powder treatment: Take the carbon rod from step (5) out of the mold, place it in a closed environment with a humidity of 75% for 24 h, and then put it in a 90℃ oven for 4 h. (7) Plasma surface treatment: The carbon rod from step (6) is placed in a low-temperature plasma treatment device and subjected to plasma surface treatment in an oxygen-containing atmosphere; (8) Post-processing: Cut the carbon rods from step (7) into the target length, wrap the filter element with non-woven fabric, and seal both ends.

2. The preparation method according to claim 1, characterized in that, The coconut shell activated carbon mentioned in step (1) has an iodine value ≥1050 mg / g and is composed of 80-200 mesh carbon powder and 200-250 mesh carbon powder, wherein the mass percentage of 80-200 mesh carbon powder is 65%-85% and the mass percentage of 200-250 mesh carbon powder is 15%-35%.

3. The preparation method according to claim 1, characterized in that, The intrinsic viscosity of the ultra-high molecular weight polyethylene in step (2) is 1500-3500 ml / g, and the melt index of the low density polyethylene is 0.1-5 g / 10min; the pore-forming agent is composed of sodium bicarbonate and starch, wherein the mass percentage of sodium bicarbonate is 97% and the mass percentage of starch is 3%; the lubricant is polyethylene wax or food-grade stearic acid.

4. The preparation method according to claim 3, characterized in that, The mass concentration of the KCl and ZnSO4 mixed solution in step (3) is 10% to 30%, the mass ratio of KCl to ZnSO4 is 1:2, and the stirring time is 10 to 16 h.

5. The preparation method according to claim 1, characterized in that, The pressing pressure in step (4) is 10–30 MPa; the gradient sintering includes the following stages:   Stage 1: Heat to 100-150℃ at a heating rate of 30-50℃ / h, and hold for sintering for 30 min; Stage 2: Increase the temperature to 180-220℃ at a heating rate of 50-80℃ / h, and hold for sintering for 75 minutes; Stage 3: Cool down to 65-80℃ at a rate of 30-60℃ / h, and hold for sintering for 30 minutes.

6. The preparation method according to claim 5, characterized in that, The pressing pressure in step (4) is 20 MPa, and the sintering temperature in stage two is 220 °C.

7. The preparation method according to claim 1, characterized in that, The plasma surface treatment in step (7) uses a low-temperature plasma jet treatment device, the treatment atmosphere is air or oxygen, the gas flow rate is 50-100 cc / min, and the treatment time is 2-10 min.

8. The preparation method according to claim 7, characterized in that, The plasma surface treatment described in step (7) employs a two-stage process: First stage: The distance from the plasma jet outlet to the carbon rod surface is 10-20 mm, and the carbon rod surface is uniformly treated at a scanning speed of 10-20 mm / s for 2-5 min. Second stage: Adjust the distance from the plasma jet outlet to the carbon rod surface to 150-200 mm and continue processing for 2-4 minutes.

9. The preparation method according to claim 1, characterized in that, Step (7) The carbon rod after plasma surface treatment has a gradient dense structure. The inner layer is a porous adsorption layer with a porosity of 45% to 55%; the outer layer is a dense anti-detachment layer formed by plasma treatment with a thickness of 0.3 to 0.8 mm and a porosity of 25% to 35%.

10. A black water-free sintered activated carbon rod for a water purifier, characterized in that, Prepared by the preparation method according to any one of claims 1 to 9.